Prevenção às drogas: análise da literatura acadêmica brasileira - Silva, Marcos Leandro da (2015)
This research examined the production of drug prevention concept in the brazilian academic literature. The choice of theme drug prevention is justified for being a controversial, paradoxical theme present in daily life and in the media headlines. This is a bibliographic search that was produced from a database in the Virtual Health Library (VHL). In this database were selected eighty (80) national references with the theme drug prevention, which were analyzed from the theoretical and methodological framework of discursive practices and production of meanings. For methodological discussion we used analyses frames as visualization strategy of the identified references, with the intention to help identifying formal aspects of linguistic construction and language repertoires and also to help on discussion of the production of meaning. The repertory language are the basic units of discourse analysis, vocabulary, expressions, figures of speech, defined as fluid, flexible organizations working to differentiate content and processes in speeches. The theorical discussion about drug prevention were done from the ideia of risk presented by Spink and Castiel also from the concept of health/disease and normal/patologic by Canguilhem. The study concludes that drugs prevention appears in academic literature associated with avoidance to risk, whit terms like protective factors and risk factors among people that use drugs, but the literature presentsno concepts of what prevention or drug prevention is.